The Algebraic Thinking Process in Solving Hots Questions Reviewed from Student Achievement Motivation - Hadi, Windia; Faradillah, Ayu (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
This research is a preliminary study that aims to describe the algebraic thinking process of prospective mathematics teachers. This research is a qualitative descriptive study. Subjects were grouped into two categories based on high and low achievement motivation. Data is obtained based on the results of tests conducted in the algebra process. Research subjects (S1) and (S2) with high achievement motivation and subjects (S3) and (S4) with low achievement motivation using different algebraic thought processes. Subjects (S1) are able in the process of thinking algebra until crashing indicators assess understanding with understanding of the concept wrong in solving Higher Order Thinking Skills (HOTS) problems, whereas, (S2) the process of thinking algebra is only capable of chunking information (pieces of information), (S3) able in the process of thinking algebra until indicators of change with wrong answers, and the subject (S4) is able in the process of thinking algebra only until chunking information (pieces of information). Factors that cause subjects S1, S2, S3, and S4 are still unable to solve HOTS questions in algebraic thinking processes are questions of knowledge on HOTS material and difficulty understanding concepts in working on algebra need special handling in improving understanding of concepts in algebra.